2020
DOI: 10.12930/nacada-18-26
|View full text |Cite
|
Sign up to set email alerts
|

Insider Information: Advisors' Perspectives on the Effectiveness of Enhanced Advising Programs for Community College Students

Abstract: This study examines the structure of an enhanced advising program (EAP) through the perspectives of academic advisors. Utilizing a qualitative research design, interviews were conducted with 12 primary-role academic advisors employed within an EAP at a large, urban community college in Texas. Thematic analysis of the interviews identified the following distinguishing characteristics of EAPs: (1) improved student participation in academic advising; (2) stronger student engagement with advising; and (3) proactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
0
11
0
2
Order By: Relevance
“…The number of faculty advisors has also increased to fifteen with some advising posts still being funded by the University Capacity Development Programme of the Department of Higher Education. Donaldson et al (2020) thus acknowledge that advising is characterised by a high student-advisor ratio. Over an eight-year period, capacity has increased but a high student-advisor ratio remains.…”
Section: Organisational Structures and Delivery Systemsmentioning
confidence: 99%
“…The number of faculty advisors has also increased to fifteen with some advising posts still being funded by the University Capacity Development Programme of the Department of Higher Education. Donaldson et al (2020) thus acknowledge that advising is characterised by a high student-advisor ratio. Over an eight-year period, capacity has increased but a high student-advisor ratio remains.…”
Section: Organisational Structures and Delivery Systemsmentioning
confidence: 99%
“…The researchers underlined that shareholders needed to go beyond comprehending the features of new technologies and that they must understand how the new technologies operate so that they can apply them strategically. Donaldson et al [25] examined academic advisors' perspectives on enhanced advising programs, wherein they found that for an improved advising experience, students needed to participate and engage in constructing a proactive educational plan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to a wide variety of advising structures, a diverse array of advising approaches exists (Alvarado & Olson, 2020;Donaldson et al, 2020;Grites, 2013;Harris, 2018;Varney, 2013). Some advisors see their roles as prescriptive in which the function of their position is to relay information to students (Alvarado & Olson, 2020;Harris, 2018;.…”
Section: Advising Approachesmentioning
confidence: 99%
“…Specifically, role allocation and organizational structuring are found to be contributors to inequity within organizations (Amis et al, 2020). As the work of the advisor grows increasingly relational (Alvarado & Olson, 2020;Donaldson et al,2020;Grites, 2013;Harris, 2018;Varney, 2013) and women are often sorted into relational roles (Qian & Fan, 2018), the relationship building performed by women is frequently seen as kindness, as opposed to the value-added work of a professional (Bernhagen & Gravett, 2017;Larson, 2008). Academic advising is female dominated NACADA Membership Demographic Information, 2019) and, as the work of women is historically undervalued in the university system (Bernhagen & Gravett, 2017;, it is reasonable to explore gender in relation to professionalization challenges.…”
Section: Gender Representationmentioning
confidence: 99%
See 1 more Smart Citation